Improving Students' Speaking Skills in Indonesian Language Content Using the Purun Model in Grade V of Elementary School - City Rahmah, Desi Davitalia (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
The problem of this research is the low level of speaking skills which affects students' activities and learning outcomes in Indonesian language content. The purpose of this study is to describe teacher activities, analyze activities, speaking skills, and student learning outcomes. This research used Classroom Action Research (CAR) and was conducted in 4 meetings. The subjects of this research were fifth grade students. Qualitative data collection was obtained from the results and tests. Data analysis in this study used qualitative and quantitative techniques. The results of this study showed that the teacher's activity received a score of 32 with very good criteria, student activity increased to 100% with the criteria that all students were active, students' speaking skills increased to the criteria that all students were skilled, students' cognitive learning outcomes increased to 100%, affective learning outcomes increased to 90%, and psychomotor learning outcomes increased to 90%. Based on the results of this study, it is concluded that the PURUN model (Problem Based Learning, Picture and picture, and Time Token) can improve students' speaking skills.